Pemahaman Terhadap Praktik Demokrasi Gen Z Pada Pemilihan Legislatif Tahun 2024: Studi Kasus Pertukaran Mahasiswa Merdeka 4 di Universitas Negeri Medan - Marly Meani Silalahi; San Mikael Sinambela; Johan Pardamean Simanjuntak; Esra Natasya Br Sitepu; Jojor Mindo Manullang; Chairun Nisa (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This research explores Gen Z's understanding of democratic practices in the 2024 Legislative Election, focusing on the Merdeka Student Exchange 4 program at Universitas Negeri Medan. The primary focus is identifying the high political awareness, active participation, and critical attitudes of participating students. The research methods include in-depth interviews, participatory observation, and quantitative data analysis from structured surveys. Findings indicate that Gen Z holds a more pragmatic and critical view of the democratic process compared to previous generations, with particular attention to transparency and accountability. Participation in the exchange program significantly enhances students' understanding of political pluralism and tolerance. These findings are crucial for developing more effective and inclusive political education strategies, aimed at encouraging greater youth participation in the democratic process.